2016
DOI: 10.1016/j.molmet.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The diabetes medication Canagliflozin reduces cancer cell proliferation by inhibiting mitochondrial complex-I supported respiration

Abstract: ObjectiveThe sodium-glucose transporter 2 (SGLT2) inhibitors Canagliflozin and Dapagliflozin are recently approved medications for type 2 diabetes. Recent studies indicate that SGLT2 inhibitors may inhibit the growth of some cancer cells but the mechanism(s) remain unclear.MethodsCellular proliferation and clonogenic survival were used to assess the sensitivity of prostate and lung cancer cell growth to the SGLT2 inhibitors. Oxygen consumption, extracellular acidification rate, cellular ATP, glucose uptake, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
143
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 41 publications
(59 reference statements)
13
143
2
4
Order By: Relevance
“…Therefore, we consider the suppression of AKT phosphorylation to be highly relevant to canagliflozin‐mediated apoptosis in liver cancer cells. A recent report discussed different mechanism by which canagliflozin could inhibit prostate and lung cancer cell growth independently of glucose uptake and AKT dephosphorylation via AMPK activation and mitochondrial respiration inhibition . However, our current results showed no significant effect of canagliflozin on AMPK activation (data not shown).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Therefore, we consider the suppression of AKT phosphorylation to be highly relevant to canagliflozin‐mediated apoptosis in liver cancer cells. A recent report discussed different mechanism by which canagliflozin could inhibit prostate and lung cancer cell growth independently of glucose uptake and AKT dephosphorylation via AMPK activation and mitochondrial respiration inhibition . However, our current results showed no significant effect of canagliflozin on AMPK activation (data not shown).…”
Section: Discussioncontrasting
confidence: 89%
“…Accordingly, SGLT2‐Is, which target this process, offer unique benefits as blood glucose‐lowering agents and are currently under development as adjuncts to standard care for patients with T2DM. Although normally, SGLT2 is predominantly localized in the kidney, recent studies have revealed SGLT2 expression in certain types of cancer cells; furthermore, inhibition of this transporter can suppress cancer growth . Regarding liver cancers, in our study we observed SGLT2 upregulation in human liver cancer cells relative to PHH and hepatic stellate cells, and found that canagliflozin‐mediated SGLT2 inhibition suppressed intracellular glucose uptake in a dose‐dependent manner.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Increases in fatty acid synthesis are required to sustain rapid proliferation in many types of cancer [for review, see (Hanahan and Weinberg, 2011; Hirschey et al ., 2015)] including prostate and non‐small‐cell lung cancer (NSCLC) (Shah et al ., 2016; Svensson et al ., 2016; Villani et al ., 2016). Rates of fatty acid synthesis are governed by the expression of ATP‐citrate lyase (ACLY), acetyl‐CoA carboxylase (ACC), and fatty acid synthase (FAS) (Hanahan and Weinberg, 2011; Hirschey et al ., 2015; Shah et al ., 2016; Svensson et al ., 2016; Villani et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rates of fatty acid synthesis are governed by the expression of ATP‐citrate lyase (ACLY), acetyl‐CoA carboxylase (ACC), and fatty acid synthase (FAS) (Hanahan and Weinberg, 2011; Hirschey et al ., 2015; Shah et al ., 2016; Svensson et al ., 2016; Villani et al ., 2016). While AMPK may regulate multiple branches of the lipogenic pathway, direct phosphorylation of ACC has been shown to result in the inhibition of ACC activity, thereby preventing the conversion of acetyl‐CoA to malonyl‐CoA and blocking the entire lipogenic program (Fullerton et al ., 2013; Munday et al ., 1988).…”
Section: Introductionmentioning
confidence: 99%